Bulbul Memorial Museum as a Center of Cultural and Historical Memory - Fargana Jabbarova (Культура і мистецтво у сучасному світі, 2024)
The aim of the article is to study and introduce into scientific circulation information about the current activities of the Bulbul Memorial Museum regarding the preservation of the musical heritage of the founder of the professional vocal art of Azerbaijan. The material base of the study consists of the exposition of the Bulbul Memorial Museum and archival sources. Results. The article examines the history of creation and the current activities of the Bulbul Memorial Museum in Shusha after the occupation. The exposition of the museum is characterised, which presents Bulbul’s personal belongings, materials reflecting his creative, scientific, educational and social activities. The article provides a brief overview of the artist’s creative achievements, and also examines Bulbul’s documents and works. In particular, the article begins a discussion about such a peak of Bulbul’s work as the opera “Keroglu”. The activities of the Research Music Cabinet, which plays an indispensable role in the history of the musical culture of Azerbaijan, are highlighted. Information is provided on the unique exhibits known as phonograph records, which are well preserved at the Bulbul Memorial Museum. Scientific novelty. For the first time, the role of information technologies in the presentation of the Bulbul Memorial Museum is studied through the prism of preserving the musical heritage of the founder of professional vocal art of Azerbaijan. Conclusions. The Bulbul Memorial Museum in Shusha contains a powerful display of personal things and documents highlighting Bulbul’s musical legacy as the founder of professional vocal art in Azerbaijan. The use of information technologies for the presentation of the museum’s exposition meets modern requirements of museum activity. The use of a modern technological tool in the Bulbul house-museum — a monitor with a touch screen — is an important feature that arouses interest in the museum.